2018
DOI: 10.18632/oncotarget.24093
|View full text |Cite
|
Sign up to set email alerts
|

Chronic feeding with protein-restricted diets affect ileal amino acid digestibility and the expression of nutrient-sensing, hormone secretion, gastrointestinal digestive enzyme, and nutrient transporter genes in young weaned pigs

et al.

Abstract: The aim of this work was to investigate the serum biochemical profile, ileal amino acid (AA) digestibility, and expression of nutrient-sensing, hormone secretion, gastrointestinal (GIT) digestive enzyme and nutrient transporter genes in pigs subjected to dietary protein restriction. Twenty-four weaned pigs were distributed into three treatments, and the animals in each treatment were fed crude protein (CP) diets at one of three levels (20, 17, and 14%). Our results showed that pigs fed the 20% CP diet had grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 57 publications
(126 reference statements)
2
10
0
Order By: Relevance
“…Slightly low-protein (SLP) diets (reduced crude protein (CP) by 4% unit) supplemented with the first four limiting amino acids (LAA), i.e., lysine (Lys), methionine (Met), threonine (Thr), and tryptophan (Trp), have been suggested for reducing nitrogen (N) excretion from swine production [ 1 ] without having a negative influence on the growth performance of pigs [ 2 ]. While decreasing dietary CP by more than 4% unit may produce a higher reduction in N excretion than SLP diets in pigs [ 3 ], very-low-protein (VLP) diets fail to maintain normal growth in pigs even when supplemented with first four LAA [ 4 , 5 , 6 , 7 ]. This could be the indication of the importance of next LAA for maintaining the optimal growth of pigs under VLP diets.…”
Section: Introductionmentioning
confidence: 99%
“…Slightly low-protein (SLP) diets (reduced crude protein (CP) by 4% unit) supplemented with the first four limiting amino acids (LAA), i.e., lysine (Lys), methionine (Met), threonine (Thr), and tryptophan (Trp), have been suggested for reducing nitrogen (N) excretion from swine production [ 1 ] without having a negative influence on the growth performance of pigs [ 2 ]. While decreasing dietary CP by more than 4% unit may produce a higher reduction in N excretion than SLP diets in pigs [ 3 ], very-low-protein (VLP) diets fail to maintain normal growth in pigs even when supplemented with first four LAA [ 4 , 5 , 6 , 7 ]. This could be the indication of the importance of next LAA for maintaining the optimal growth of pigs under VLP diets.…”
Section: Introductionmentioning
confidence: 99%
“…For example, cholesterol and triglycerides are indicators of lipid metabolism [ 42 ], and urea nitrogen is an indicator of protein utilization efficiency [ 43 ]. Although biochemical parameters are influenced by various factors such as age, sex, and nutrition [ 38 , 41 ], the results of this study showed that replacing corn with rice does not have a negative effect on biochemical parameters.…”
Section: Resultsmentioning
confidence: 87%
“…According to Tao et al [ 40 ], it was reported that the serum biochemical parameters of piglets gradually decreased for one week after weaning, but as a result of this study, it is considered to be recovered to the normal levels after 2 week of weaning. Biochemical parameters are related to nutrient metabolism and utilization [ 41 ]. For example, cholesterol and triglycerides are indicators of lipid metabolism [ 42 ], and urea nitrogen is an indicator of protein utilization efficiency [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreasing blood urea nitrogen and ammonia levels in the colon also showed that nitrogen excretion was reduced. Combined with the observed lower growth performance in piglets from another study, this indicates that a reduced protein content of 3% supplemented with lysine, methionine, threonine and tryptophan corresponds to an alternative feeding recommendation [ 24 , 87 ]. It also suggests that improvements in nutrient digestibility results from changes in nutrient transporter and enzyme gene expression as well as a change in microbial activity [ 67 ].…”
Section: Conclusion and Perspectivementioning
confidence: 98%